Structural details and magnetic order of La1-xSrxCoO3 (x <= 0.3) - Caciuffo, R; Rinaldi, D; Barucca, G; Mira, J; Rivas, J; Senaris-Rodriguez, M; Radaelli, P; Fiorani, D; Goodenough, J (1999)
The crystallographic structure and the magnetic order of the distorted perovskite La1-xSrxCoO3 (0.10≤x ≤0.30) has been studied by neutron diffraction, high-resolution electron microscopy, and magnetic-susceptibility measurements. The results give direct evidence for an inhomogeneous distribution of the Sr2+ ions and the segregation of the material into hole-rich ferromagnetic regions and a hole-poor semiconducting matrix at lower values of x. The holes introduced by Sr doping are attracted to the Sr2+ ions where they stabilize to lowest temperatures an intermediate-spin state at neighboring trivalent cobalt. The antibonding e electrons so stabilized increase the mean unit-cell volume and are delocalized over the cobalt atoms of the cluster where they couple the localized t5 configurations ferromagnetically. Long-range ferromagnetic order between clusters is realized even for Sr doping as low as x=0.10. The transition to a spin glass state is observed only for Sr concentrations smaller than 0.10. The volume of a hole-rich cluster grows in a magnetic field, and the origin of the large negative magnetoresistance observed near Tc for 0.15 ≤ x ≤ 0.25 appears to be due to a growth of the clusters to a percolation threshold. For x=0.30, the σ* band of the intermediate-spin state below Tc is at the threshold of a transition from itinerant to polaronic conduction and, above Tc, the system transforms smoothly to a cluster state. © 1999 The American Physical Society.